2019
DOI: 10.15171/apb.2019.058
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Thymoquinone on Viability, and Anti-apoptotic Factors (BCL-XL, BCL-2, MCL-1) in Prostate Cancer (PC3) Cells: An In Vitro and Computer-Simulated Environment Study

Abstract: Purpose: Since active plant ingredients can induce apoptosis in many tumors, in this study we evaluate the apoptotic effects of thymoquinone (TQ) on PC3 cells. Also, we predicted the interaction of TQ with BCL-XL, BCL-2, and MCL-1anti-apoptotic factors by computer-simulated environment. Methods: PC3 cells were treated with different concentrations of TQ (0- 80 µM) and IC50 was determined using 3-(4, 5-dimethylthiaztol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Apoptotic and cytotoxicity effects of TQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Notably, a significant reduction in cell viability was observed in the concentration range of 50 to 210 μM for HCT-15, which is consistent with the findings in the HCT-116 cell line reported by Özkoç [ 64 ], who observed a marked decrease in cell viability in the range of 60 to 200 µM, and the IC 50 value for TQ was determined to be 68 µM at 24 h [ 64 ]. Additionally, Saffari-Chaleshtori [ 60 ] showed a notable decrease in cell viability in a range of 20 to 70 μM for PC3 cell lines, reporting an IC 50 of 40 μM, which is consistent with our assay obtaining an IC 50 of 55.83 μM. This similarity in the concentration range and the IC 50 values supports the notion that TQ exerts a comparable inhibitory effect on the proliferation of colon and prostate cancer cell lines.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Notably, a significant reduction in cell viability was observed in the concentration range of 50 to 210 μM for HCT-15, which is consistent with the findings in the HCT-116 cell line reported by Özkoç [ 64 ], who observed a marked decrease in cell viability in the range of 60 to 200 µM, and the IC 50 value for TQ was determined to be 68 µM at 24 h [ 64 ]. Additionally, Saffari-Chaleshtori [ 60 ] showed a notable decrease in cell viability in a range of 20 to 70 μM for PC3 cell lines, reporting an IC 50 of 40 μM, which is consistent with our assay obtaining an IC 50 of 55.83 μM. This similarity in the concentration range and the IC 50 values supports the notion that TQ exerts a comparable inhibitory effect on the proliferation of colon and prostate cancer cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…The focus on utilizing plant extracts, such as TQ derived from Nigella sativa , as a potential source of anticancer compounds offers promising prospects [ 23 ]. Several research studies have demonstrated that TQ possesses the ability to suppress cell proliferation and enhance apoptosis in malignant cells [ 60 , 61 , 62 , 63 ]. Prior research has demonstrated that TQ can induce dose-dependent cell death in colon and prostate cancer cell models, including the HCT-116 human colorectal carcinoma cell line, the HT-29 human colorectal adenocarcinoma cell line, and the PC3 prostatic adenocarcinoma cell line [ 60 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The voacangine has a simpler structure, this is what makes it easier for voacangine to enter the binding site of the Bcl-2 receptor. This statement is supported by (Saffari-Chaleshtori et al, 2019) who reported the inhibitory activity of thymoquinone against Bcl-2. Even though when interacting with the Bcl-2 receptor, this compound does not form hydrogen bonds at all, this compound has a simple spatial structure that allows easy entry to the Bcl-2 receptor binding site.…”
Section: Molecular Docking Studymentioning
confidence: 55%
“…In castration-resistant and androgen-independent Pca, as in the case of PC-3 cells, MCL-1 is upregulated, resulting in resistance to apoptosis and a worse prognosis (65). Other authors have showed increased apoptosis in PC-3 cells after treatment with thymoquinone, an agent capable of negatively regulating MCL-1 (66). Other studies also demonstrate higher cell death rates in PC-3 cells after treatment with drugs that inhibit MCL-1 (67,68).…”
Section: Protein-protein Interactions (Ppi) Network and Pathway Analysismentioning
confidence: 99%